Minimally Invasive Surgery in Endometrial Cancer: Superior for Low-Risk and Comparable for High-Risk Cases in a 20-Year Cohort Study - Auletta, Valentina; Hassan, Maya Ehab; Kather, Angela; Gaßler, Nikolaus; Bokhua, Davit; Runnebaum, Ingo B. (Geburtshilfe und Frauenheilkunde, 2025)
Minimally invasive surgery (MIS) to treat endometrial cancer offers advantages over laparotomy, although concerns about its oncological safety for high-risk tumors and feasibility in patients with significant comorbidities remain. This study evaluates perioperative and long-term outcomes of MIS versus open surgery in a tertiary referral center cohort, using FIGO 2010 and 2023 classifications.This is a retrospective analysis of perioperative outcomes, recurrence rates, and survival after endometrial cancer surgery (2000–2021) at an ESGO training center and tertiary referral center in Germany. 760 patients underwent hysterectomy, and adequate data for risk classification (without molecular diagnostics) was available for 330 of them.More than one third of the patients were aged 70 years or older and approximately half of the patients were obese. A high proportion presented with comorbidities such as hypertension or diabetes. MIS demonstrated favorable perioperative results in both low-risk and high-risk patients. Survival analysis showed a superior outcome with MIS for low-risk (5-year RFS rate: 79.8% vs. 59.2%, p = 0.035; OS rate: 83.8% vs. 58.0%, p = 0.010) and FIGO 2023 stage I disease (OS: p = 0.014). The oncological safety of MIS was equivalent to that of open surgery for high-risk tumors (5-year RFS rate: 60.5% vs. 54.3%, p = 0.506; OS rate: 67.5% vs. 58.3%, p = 0.416) and FIGO 2023 stages II (RFS, p = 0.453; OS, p = 0.378) and III (RFS, p = 0.419; OS, p = 0.850).MIS was found to have superior outcomes for low-risk endometrial cancer and a comparable safety for high-risk patients, including those with older age or significant comorbidities. These findings support the use of MIS approaches as viable options across diverse risk groups, in line with FIGO 2023.
Keywords: endometrial cancer; minimally invasive surgery; high risk cases; laparoscopy; laparotomy